Urban women's socioeconomic status, health service needs and utilization in the four weeks after postpartum hospital discharge: findings of a Canadian cross-sectional survey - Ciliska Donna; Sword Wendy; Kurtz Landy Christine (BMC, 2008)
Abstract Background Postpartum women who experience socioeconomic disadvantage are at higher risk for poor health outcomes than more advantaged postpartum women, and may benefit from access to community based postpartum health services. This study examined socioeconomically disadvantaged (SED) postpartum women's health, and health service needs and utilization patterns in the first four weeks post hospital discharge, and compared them to more socioeconomically advantaged (SEA) postpartum women's health, health service needs and utilization patterns. Methods Data collected as part of a large Ontario cross-sectional mother-infant survey were analyzed. Women (N = 1000) who had uncomplicated vaginal births of single 'at-term' infants at four hospitals in two large southern Ontario, Canada cities were stratified into SED and SEA groups based on income, social support and a universally administered hospital postpartum risk screen. Participants completed a self-administered questionnaire before hospital discharge and a telephone interview four weeks after discharge. Main outcome measures were self-reported health status, symptoms of postpartum depression, postpartum service needs and health service use. Results When compared to the SEA women, the SED women were more likely to be discharged from hospital within the first 24 hours after giving birth [OR 1.49, 95% CI (1.01-2.18)], less likely to report very good or excellent health [OR 0.48, 95% CI (0.35-0.67)], and had higher rates of symptoms of postpartum depression [OR 2.7, 95% CI(1.64-4.4)]. No differences were found between groups in relation to self reported need for and ability to access services for physical and mental health needs, or in use of physicians, walk-in clinics and emergency departments. The SED group were more likely to accept public health nurse home visits [OR 2.24, 95% CI(1.47-3.40)]. Conclusion Although SED women experienced poorer mental and overall health they reported similar health service needs and utilization patterns to more SEA women. The results can assist policy makers, health service planners and providers to develop and implement necessary and accessible services. Further research is needed to evaluate SED postpartum women's health service needs and barriers to service use.